Discriminação de raças primitivas de Pupunha (Bactris Gasipaes) na Amazônia brasileira por meio de marcadores moleculares (RAPDs) - Sousa, Nelcimar R. (Acta Amazonica, 2020)
The pejibaye (Bactris gasipaes Kunth, Palmae) was domesticated for it fruits by the first peoples of western Amazonia. Consequently it exhibits a landrace complex that has been partially characterized morphologically and mapped. Along the Amazonas and Solimões Rivers, in Brazil, three landraces have been proposed [Pará (Amazonas River), Solimões (lower and middle Solimões River), Putumayo (upper Solimões River)], with indications that the Solimões landrace could be an artifact of the morphometric analysis. RAPD markers were used to evaluate the three landrace hypothesis. DNA was extracted from 30 plants of each landrace maintained in the Pejibaye germplasm bank, Manaus, AM, Brazil. During PCR amplification, 8 primers generated 80 markers, Jaccard similarities were estimated, the plants were grouped with UPGMA. The dendrogram contained 2 large groups that joined at a similarity of 0.535: the group of the Pará landrace contained 26 plants of this race, 5 of the Putumayo and 1 of the Solimões; the group of the Solimões River contained 29 plants of the Solimões race, 19 of the Putumayo and 1 of the Pará. The structure of the second group suggested that there is only one landrace along the Solimões River, since the plants were mixed in sub-groups without apparent order. This marker-based genetic analysis did not support the three landrace hypothesis and suggests that the Putumayo landrace extends along the Solimões River to central Amazonia. Genetic and morphological data must now be used to evaluate this new hypothesis.